ELEVATION CHARACTERISTICS AND MORPHOLOGICAL TYPES OF GLACIERS OF THE KARADARYA BASIN (Scientific journal of the Fergana State University, 2025)
The article analyzes the changes in the elevation characteristics of glaciers in the Karadarya basin on the southwestern slopes of the Fergana Range and the northern slopes of the Aloy Range. Changes in the elevation characteristics and morphological types of mountain glaciers located in the river basin were compared based on data from 1970 and 2016. At the same time, changes in the general exposure of glaciers located in the basin were also analyzed. The study widely used geographical comparison, historical approach, and statistical analysis methods.